If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying t + 13.4 = -4.5 Reorder the terms: 13.4 + t = -4.5 Solving 13.4 + t = -4.5 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13.4' to each side of the equation. 13.4 + -13.4 + t = -4.5 + -13.4 Combine like terms: 13.4 + -13.4 = 0.0 0.0 + t = -4.5 + -13.4 t = -4.5 + -13.4 Combine like terms: -4.5 + -13.4 = -17.9 t = -17.9 Simplifying t = -17.9
| 1p-5=8 | | 4(p+5)=7 | | 36t^2=9 | | -6n+5n=-3 | | 4(p+-5)=7 | | (6x-6)(4x+9)=0 | | -6r+5s+2t=-11 | | 3(x)=8.25 | | 3x^2-6x+4y^2-13=0 | | 12(y+2)=36 | | 8(x)=8.25 | | 8x+7=127 | | 170+0.25x=375 | | 7200=(756)R(2.5) | | x-8.6=4.1 | | y+5x=-10 | | -2/3+x=22/3 | | 5665*x=100000 | | 6z+17=-7 | | 12d-7+3d=19+14d | | 49x^2-10=0 | | x-.07=139500 | | -2(x-1)-4=-4(1+x)+2x+2 | | x+100=299 | | 2x-3(2x+4)=-6x+10 | | r+34=21 | | 3y+5(-3)y-3=27 | | 4u-w=u-5w | | 79/7=x-5/7 | | 420+d=-196 | | 24m+85=685 | | 2(v-5)-4=-5(-4v+1)-6v |